Sustainable Management of Groundwater Resources in the Gash Basin, Sudan - ALmahi, Mojahid M.S.; Al Kabier, Mohieldin A.E.; Ahmed, Shamseddin M. (Gezira Journal of Engineering and Applied Sciences, 2021)
In the Gash Basin, Kassala State, Sudan; Domestic and horticultural irrigation water supplies depend entirely on groundwater. The basin is annually recharged from the Gash River which is shared with Eritrea, Sudan and Ethiopia. Recently, groundwater level has been significantly dropped in the unconfined Gash aquifer in Sudan due to over pumping. The objectives of this study were to determine the future safe utilizable amounts of groundwater under different developed scenarios by the year 2050, to investigate the sensitivity of the aquifers to changes in the recharging rates and to develop a sustainable operation plan. Datasets of 1194 discharging wells and 51 observation wells were collected and analyzed. A one-layer conceptual model was built for representing the unconfined aquifer based on the Modflow model. The calibration and validation of the model were carried out via the hydraulic heads of 12 observation wells (2008 – 2017). The results showed that due to the decreasing trend in the Gash River flows of 9% in the period 2000 –2018, the recharging rate experienced a decrease of 0.7%. The scenario “running the business as usual” stated a drawdown of 2m to 13 m relative to the year 2018.  To stabilize the current head, annual recharge amounts of 228 million m 3 is required. Under the conditions that there is no recharge (no stream flows of the Gash River), a drawdown up to 20% will occur. Spatially, the upstream and middle parts of the River were the most sensitive part of the no recharging conditions. The described sustainable operation model of this study is recommended for managing groundwater resources in the Gash basin, Sudan.